Conditional Deletion of PDK1 in the Forebrain Causes Neuron Loss and Increased Apoptosis during Cortical Development - Xu, Congyu; Yu, Linjie; Hou, Jinxing; Jackson, Rosemary J.; Wang, He; Huang, Chaoli; Liu, Tingting; Wang, Qihui; Zou, Xiaochuan; Morris, Richard G.; Spires-Jones, Tara L.; Yang, Zhongzhou; et al. (Frontiers in Cellular Neuroscience, 2017)
Decreased expression but increased activity of PDK1 has been observed in neurodegenerative disease. To study in vivo function of PDK1 in neuron survival during cortical development, we generate forebrain specific PDK1 conditional knockout (cKO) mice. We demonstrate that PDK1 cKO mice display striking neuron loss and increased apoptosis. We report that PDK1 cKO mice exhibit deficits on several behavioral tasks. Moreover, PDK1 cKO mice show decreased activities for Akt and mTOR. These results highlight an essential role of endogenous PDK1 in the maintenance of neuronal survival during cortical development.